Varnost in sodelovanje v jugovzhodni Evropi - Grizold, Anton (Teorija in praksa, 1998)
The term Southeastern Europe contains different dimensions: geographical, socio-political, cultural, military etc. The author defines the term as a transitional character of the countries in the region and focuses on the Balkan core and its neighbourhood. The aim of the article is to emphasize some of the important problems as well as different activities, which are needed to stimulate the new spirit of co-operation, economic initiative and institutional solutions in order to strenghten stability in the Balkans as well as in the whole region of Southeastern Europe. The author deals firstly with southeastern security frame: control over the weapon, reassurance, responsibility and progress on the way to renewed consolidation of relations between three main participants in the conflict - BiH, ZRJ and Croatia. Since Slovenia is at an important crossroad, which geographically, politically, economically and culturally links together central and southeastern parts of Europe, it can significantly influence peace and stability in the Balkan region. The author thus especially points out the role of Slovenian foreign and security policies. Finally, the author attempts to develop complete, strategic approach to peace in Europe, which includes among others also a problem of refugees, reinstatement of peace etc.
Keywords: Slovenia; Slovenija; Jugovzhodna Evropa; mednarodni sporazumi; mednarodni odnosi; nadzor nad oboroževanjem; mednarodna varnost; nacionalna varnost